Distribution change and protected area planning of Tilia amurensis in China: A study of integrating the climate change and present habitat landscape pattern - Bingrui Chen; Hui Zou; Boyan Zhang; Xiyuan Zhang; Chen Wang; Xinxin Zhang (Global Ecology and Conservation, 2023)
Tilia amurensis is a national class II endangered plant in China. It plays an essential role in maintaining the stability of regional forest communities. Moreover, it is an essential economic tree species in Northeast Asia. In recent years, the impact of rapid climate change on the distribution and adaptability of plant populations has received increasing attention. However, there is still a knowledge gap in our understanding of the future distribution changes of this important species. In this study, we used the ensemble species distribution model to simulate the distribution of T. amurensis in China under different climate scenarios. In addition, we used Fragstats and Zonation software based on the result of the ensemble species distribution model and combining the multi-year land use data. Using this method, we can clarify the landscape pattern changes and priority protection areas of T. amurensis. The results showed that the suitable area of T. amurensis in China was mainly located in the northeast region. The area of forest habitat suitable for T. amurensis has gradually decreased, and the fragmentation degree has progressively increased over the past 40 years. Under the background of future climate change, the suitable area of T. amurensis could move progressively to high latitude and high altitude, and the total area could show an upward trend. However, the area of the high suitable area could decrease sharply with the increase of year and carbon emissions. Six environmental factors: altitude (Alt), precipitation in the warmest quarter (Bio18), mean temperature of the driest quarter (Bio09), min temperature of the coldest month (Bio06), temperature seasonality (Bio04), and isothermality (Bio03), play a crucial role in the spatial distribution of T. amurensis. The counties in Northeast China are the most suitable areas for protecting T. amurensis action, located in the southern Xiaoxing'an Mountains and northern Changbai Mountains counties. In addition, among the existing protected areas, Fenglin National Nature Reserve has the highest area of mandatory reserves. It is expected to become a preferred location for T. amurensis conservation actions. Our results can provide a helpful reference for the effective protection and sustainable utilization of T. amurensis under climate change.